LncRNA LINC01018 Screens Type 2 Diabetes Mellitus and Regulates β Cell Function Through Modulating miR-499a-5p - Liu, Li; Li, Yuan; Zhang, Xiaoqian (Hormone and Metabolic Research, 2023)
Type 2 diabetes mellitus (T2DM) is characterized by hyperglycemia, which seriously endangers human health. The dysregulation of lncRNA LINC01018 in T2DM has been noticed in previous studies, but whether it served as a biomarker lacks validation. This study aimed to confirm the abnormal expression of LINC01018 in T2DM and reveals its specific function in regulating pancreatic β cell function. This study enrolled 77 T2DM patients and 41 healthy individuals and compared the plasma LINC01018 levels between two groups using PCR. The pancreatic β cell was induced with 25 mM glucose to mimic cell injury during T2DM. The effects of LINC01018 on β cell proliferation, dedifferentiation, and insulin production were evaluated by CCK8, western blotting, and ELISA. Moreover, the involvement of miR-499a-5p was also evaluated with luciferase reporter assay. Increased plasma LINC01018 was observed in T2DM patients compared with healthy individuals, which discriminates patients with high sensitivity and specificity. Upregulated LINC01018 was associated with patients’ fasting blood glucose and weight loss. High glucose induced the increasing LINC01018 in pancreatic islet β cells and suppressed cell proliferation, insulin secretion, and promoted cell dedifferentiation. Silencing LINC01018 could alleviate the impaired function of β cells by high glucose, which was reversed by the knockdown by miR-499a-5p. Upregulated LINC01018 served as a potential diagnostic biomarker for T2DM and alleviated high glucose-induced β cell dysfunction via negatively modulating miR-499a-5p.
Keywords: lncRNA; diagnostic biomarker; β cell; proliferation; dedifferentiation; insulin secretion, diabetes